Changes in Some Biochemical Properties during Different Maturity Stages of Peels, Pulps and Fruits of Pomegranate (Punicegranatum) - Marwa Ali (Journal of Global Pharma Technology, 2018)
Fully ripe, mid-ripe and unripe pomegranate fruits were gathered from the fields of Hilla city Iraq during the year 2016/2017 to estimate Na, K elements and some biochemical parameters such as coumarin gallic acid and tannin ,also the peels and pulps of pomegranate for three different countries (Yemen Iraq and Egypt) were separated to determine Na, K and some biochemical compounds which analyzed by (HPLC) owing to this study the mid-ripe fruit had the highest quantity of Na and K whereas fully –ripe fruit had the highest quantity in gallic , coumarin and tannic acid Yemeni an pulp had the highest quantity of Na where, as unripe Iraq pulps had the highest amount of K  while peels and pulps of Egyptian pomegranate had the lowest amount of K element . The results of active compounds indicated that Iraq unripe peel had the highest quantity of coumarin and tannic acid compared to the others, where as they had the lowest quantity of these acids in pulp part of pomegranateKeywords: Pomegranate, Comuranin, Active compounds, Ripe and unripe fruits.